2021
DOI: 10.1039/d0nh00624f
|View full text |Cite
|
Sign up to set email alerts
|

Fusogenic porous silicon nanoparticles as a broad-spectrum immunotherapy against bacterial infections

Abstract: Bacterial infections are re-emerging as substantial threats to global health due to the limited selection of antibiotics that are capable of overcoming antibiotic-resistant strains. By deterring such mutations whilst minimizing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…Lowgrade inflammation is common in autoimmunity (145), with an inflammatory signature similar to COVID-19 (146). The therapeutic usefulness of IRF5 inhibitors is yet to be determined (13,123,(145)(146)(147)(148)175).…”
Section: Discussionmentioning
confidence: 99%
“…Lowgrade inflammation is common in autoimmunity (145), with an inflammatory signature similar to COVID-19 (146). The therapeutic usefulness of IRF5 inhibitors is yet to be determined (13,123,(145)(146)(147)(148)175).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with AgPd 0.38 nanozymes could significantly reduce the levels of these cytokines and immune-related cells and successfully lowered them close to healthy levels (Figure f–h), indicating the effective immune suppression capability on the inflammatory responses. Kim and co-workers prepared a macrophage-targeting fusogenic porous silicon (F-pSi) nanoparticle system to deliver siRNA against the Irf5 gene of macrophages. , The proinflammatory macrophage marker IRF5 was remarkably knocked down, inhibiting the inflammatory phenotype of macrophages to improve the survival rates of mice whose deep tissues were infected by S. aureus , MRSA, or P. aeruginosa .…”
Section: Nanosystems For Suppressing Excessive Immune Responses Again...mentioning
confidence: 99%
“…Besides, the authors found that the infection induced by P. aeruginosa could increase the serum levels of proinflammatory cytokines and co-workers prepared a macrophage-targeting fusogenic porous silicon (F-pSi) nanoparticle system to deliver siRNA against the Irf5 gene of macrophages. 64,65 The proinflammatory macrophage marker IRF5 was remarkably knocked down, inhibiting the inflammatory phenotype of macrophages to improve the survival rates of mice whose deep tissues were infected by S. aureus, MRSA, or P. aeruginosa.…”
Section: Nanosystems For Suppressing Excessive Immune Responses Again...mentioning
confidence: 99%
“…Reverse vaccinology (RV) is an up-to-date approach and is used to identify putative surface-associated proteins without the need to culture the microorganisms [26]. Through immunotherapy, pathogen-specific antibodies can be designed and produced; meanwhile, immunological interventions in the human immune system are trained to tackle bacterial infections by acquiring adaptive immunity [27]. The latter strategy, using vaccines in particular, holds great importance in lowering the burden of AR [28].…”
Section: Introductionmentioning
confidence: 99%